198k views
1 vote
A proportion question ​

A proportion question ​-example-1
User A Poor
by
5.0k points

1 Answer

5 votes

Answer:

because x,y,z are in continuous proportion

=> x/y = y/z

<=> xz = y² =>


(xz)/(y) =y\\\\=>(x^(3)z^(3) )/(y^(3) )=y^(3)(1)

with (1), we have:


x^(2)y^(2)z^(2)((1)/(x^(3) )+(1)/(y^(3) )+(1)/(z^(3) ))\\\\= (xyz)^(2)((1)/(x^(3) ) +(y^(3) )/(x^(3)z^(3) )+(1)/(z^(3) ))\\\\=(xyz)^(2) ((x^(3)+y^(3)+z^(3) )/(x^(3)z^(3)) )\\\\=y^(2).(x^(3)+y^(3)+z^(3) )/(xz) \\\\= xz.(x^(3)+y^(3)+z^(3) )/(xz) \\\\=x^(3)+y^(3)+z^(3)

Explanation:

User Yevhen Surovskyi
by
5.4k points